Students as consumers: The Implications of the Consumer Protection Act for Higher Education Institutions in South Africa - Reddy, Karunanidhi (South African Journal of Higher Education, 2016)
The Consumer Protection Act (CPA) lays the basis for the protection of consumer rights in South Africa and comprehensively sets out obligations for “suppliers”. There have been differing views expressed as to whether a student should be seen as a consumer. It is clear, however, that this Act applies to HEIs. This article, firstly, explores the concept of a student as “a customer/consumer”. Secondly, it examines specific aspects of the CPA which will have an impact on HEIs as service providers in the education sector. It concludes that the impact of the CPA for business is far-reaching. It also directs that HEIs must take into account the provisions of this Act, particularly with respect to the rights to: equality, generally and with regard to access; disclosure and information; fair and equal marketing practices; and fair and reasonable terms and conditions, as well as fair value and good quality. HEIs are advised to scrutinize their current practices, policies, terms and conditions, to ensure that they comply with the Act.